The Roles of Transient Receptor Potential Vanilloid 1 and 4 in Pneumococcal Nasal Colonization and Subsequent Development of Invasive Disease - Kono, Masamitsu; Nanushaj, Denisa; Sakatani, Hideki; Murakami, Daichi; Hijiya, Masayoshi; Kinoshita, Tetsuya; Shiga, Tatsuya; Kaneko, Fumie; Enomoto, Keisuke; Sugita, Gen; Miyajima, Masayasu; Okada, Yuka; et al. (Frontiers in Immunology, 2021)
Transient receptor potential (TRP) channels, neuronal stimulations widely known to be associated with thermal responses, pain induction and osmoregulation, have been shown in recent studies to have underlying mechanisms associated with inflammatory responses. The role of TRP channels on inflammatory milieu during bacterial infections has been widely demonstrated. It may vary among types of channels/pathogens, however, and it is not known how TRP channels function during pneumococcal infections. Streptococcus pneumoniae can cause severe infections such as pneumonia, bacteremia and meningitis, with systemic inflammatory responses. This study examines the role of TRP channels (TRPV1 and TRPV4) for pneumococcal nasal colonization and subsequent development of invasive pneumococcal disease in a mouse model. Both TRPV1 and TRPV4 channels were shown to be related to regulation of the development of pneumococcal diseases. In particular, the influx of neutrophils (polymorphonuclear cells) in the nasal cavity and the bactericidal activity were significantly suppressed among TRPV4 knockout mice. This may lead to severe pneumococcal pneumonia, resulting in dissemination of the bacteria to various organs and causing high mortality during influenza virus co-infection. Regulating host immune responses by TRP channels could be a novel strategy against pathogenic microorganisms causing strong local/systemic inflammation.